Development of Kaolin Clay as a Cost-Effective Technology for Defluoridation of Groundwater - Adane Adugna Ayalew (International Journal of Chemical Engineering)
Excessive fluoride in potable groundwater is a serious health problem in rural areas of many developing countries. The presence of a small amount of fluoride in potable water is beneficial to human health, but a high amount (>1.5 mg/L) has adverse effects. The present study is aimed to prepare a new cost-effective adsorbent of kaolin clay that can be used as a valuable defluoridating agent. Characterization of the prepared adsorbent was carried out using DSC, FTIR, TGA, and XRD. Also, the surface area of the adsorbent was measured by BET analysis. The clay was activated with concentrated H2SO4, and the effects of various experimental parameters such as temperature (25, 40, 50, and 60°C), pH (2, 4, 6, and 8), particle size (<0.075, 0.075–0.15, and 0.15–0.30 mm), contact time (30, 60, 90, 120, and 150 min), and dose of the adsorbents (0.5, 1, 1.5, 2.0, and 2.5 g) were investigated using a batch adsorption method. The specific surface area of raw and activated clay was found to be 10.598 m2/g and 5.258 m2/g, respectively. The optimum fluoride removal by both adsorbents was obtained at pH 4, temperature 50°C, particle size 0.075 mm, and 60 min. In both adsorbents, the degree of fluoride removal was increased with a decrease in the particle size of the adsorbent and increased contact time and dosage of the adsorbent. In all parameters, adsorption by activated clay was better than raw kaolin clay for retaining fluoride. The obtained data were well fitted with Freundlich and Langmuir isotherm models.